Compaction Characteristics of Oil Contaminated Residual Soil - Oluremi, J.R.; Adewuyi, A.P.; Sanni, A.A. (Journal of Engineering and Technology (JET), 2015)
Oil spillage during transportation, leakages of underground tanks in fuel stations as well as indiscriminate spill of spent oil in motor mechanic workshops have increasingly become very prevalent in Nigeria. This study examined the effect of oil contamination on the strength properties of lateritic soil. Crude oil was simulated by rigorously mixing engine oil, diesel, kerosene and gasoline (petrol) together in ratio 1:1:1:1. Lateritic soil samples were artificially contaminated with the simulated crude oil in the range 0 to 8% of the dry weight of soils in a step concentration of 2% and subjected to basic geotechnical laboratory tests using british standard light (BSL) and west African standard (WAS) compactive efforts. The results show a gradual increase in the proportion of gravelly formed particles while sand and silt contents decreases with increase in oil content. The plastic and liquid limits of the soils decreased as the crude oil content increased. The maximum dry densities (MDD) decreased from 1.06 - 1.03 mg/m3 and 1.12 - 1.04 mg/m3, while optimum moisture content (OMC) increased from 13.12 – 14.8% and 11.8 – 13.3% for both BS and WAS compactive efforts respectively as oil content increased. The unconfined compressive strength (UCS) of samples for both BS and WAS compactive efforts were 239.6 kN/m2 and 253.8 kN/m2 respectively and increased with oil content up to 2% and thereafter decreased with further contamination. A significant influence of oil contamination on the engineering properties of soils is evident, and remediation and reuse of contaminated soil is imperative.